Improving Variable Approaches Through The Application Of Digital Technologies In Education - Husniddin TOJIYEV (Euro Asian Journal Publishing, 2025)
This approach is extensively applied across various disciplines, including education, psychology, and economics. This article explores how variational approaches enable the consideration of multiple solutions to a single problem, examining the methodology, practical applications, and instructional tools used to teach this approach in education. The study’s findings aim to enhance the efficiency of the learning process while fostering students' ability to think independently.
Keywords: education; variability